A Proposed Rehabilitation Program for the Rehabilitation of an Anterior Cruciate Ligament Tear Injury - Hameed Oleiwi, Naeem; Makki Ati, Mokhles (International Journal of Psychosocial Rehabilitation, 2020)
The research and its importance are summarized by a group of exercises chosen in a program designed to rehabilitate and strengthen the knee joint muscles and compare them with the program in place in hospitals. The research aims to prepare a proposed program for the rehabilitation of the thigh muscles and the knee joint after the anterior cruciate ligament injury is torn, and the knee joint is one of the most common joints in the body. Exposure to athletes in particular (Samia Khalil 1990, p. 219) and to the effect of the proposed program on the knee joint and thigh muscles after injury and rehabilitation of the front cruciate ligament. The researcher assumed that the rehabilitation program had an effect on the rehabilitation of the thigh muscles after the anterior cruciate ligament rupture. The program regains the efficiency and strength of the knee joint muscles faster than the traditional program in force in the hospital, and to suit the experimental method, the nature of the study was used by the researcher on his research sample of people with rupture of the front cruciate ligament, whose number was (6) injured, using some tools and devices in his research procedures Such as the homogeneity and equivalence of the two groups, the exploratory and main experiences, the qualifying program and the tests used in the research, and after the results C and discussing it, the researcher concluded that the proposed program worked to increase the strength of the muscle groups of the thigh and rehabilitate the anterior cruciate ligament injury in the knee joint faster than the program in force in the hospital, which was shown by the tracer tests conducted on the members of the research sample. Then the researcher recommended the necessity of using fixed exercises And movement by athletes to rehabilitate an anterior cruciate ligament rupture, as the stationary increases strength and mobility increases the magnitude of the muscles, recommending workers in the field of rehabilitation to use tracer or intermediate tests in their rehabilitation programs to see the effect of the exercises used on the injured and the improvement achieved in order to make adjustments in their programs that And found